ANALISIS PERTUMBUHAN DAN KELULUSHIDUPAN LARVA LELE (Clarias gariepenus) YANG DIBERI PAKAN Daphnia SP. HASIL KULTUR MASSAL MENGGUNAKAN PUPUK ORGANIK DIFERMENTASI - Merawati VE; Muhamad Agus (LPPM Universitas Pekalongan, 2014)
This research was done for analyzing the influence of the Daphnia which is cultured by organic fertilizer like, chicken dung, rice shifting, bungkil (residue of copra after extracting oil) which were fermented prebiotic bacteria toward the growth and survival ratio of cat fish larva.... the threatment are (A) chicken dung 1.2 g/l of, rice shifting 1.2 g/l, (B) chicken dung 1.2 g/l of, bungkil 1.2 g/l, (C) chicken dung 1.2 g/l of, rice shifting 0.3 g/l, and bungkil 0.9 g/l, (D) chicken dung 1.2 g/l of, rice shifting 0.9 g/l, and bungkil 0.3 g/l, (E) chicken dung 1.2 g/l of, rice shifting 0.6 g/l, and bungkil 0.6 g/l, (F) Non-fermented Chicken dung 2,4 g/l. Three days of cat fish larva was spread in a 100x50x40 cm aquarium with 48 fish/ liter stockdensity. The Daphnia feeding was given in five times a day in adlibitum during 14 days. The result of the relative growth showed the real distinguish (p>0,05) with the best growth on treathment B. Survival ratio showed that there was no difference (p<0,05). Key word : organic fertilizer like, fermentation, cath fish of larva, growth, survival ratio.